G-CSF in patients suffering from late revascularised ST elevation myocardial infarction: final 1-year-results of the G-CSF-STEMI trial - Engelmann, Markus G.; Theiss, Hans D.; Theiss, Christine; Henschel, Volkmar; Huber, Armin; Wintersperger, Bernd J.; Schönberg, Stefan; Steinbeck, Gerhard; Franz, Wolfgang-M. (International journal of cardiology, 2010)
Aims - The aims of this trial were to investigate the effect of granulocyte colony-stimulating factor (G-CSF) on left-ventricular ejection fraction and event-free survival in patients suffering from sub-acute myocardial infarction (STEMI). - Methods - We enrolled 44 patients suffering from sub-acute STEMI with late revascularization achieved by percutaneous coronary intervention (PCI). Patients were randomized to receive either G-CSF (Filgrastim) at a dose of 10 μg/kg body weight/day subcutaneously or placebo. Changes of global and regional cardiac function from baseline (1 week after PCI) over 1 and 3 months to 12 months of follow-up were analyzed by magnetic resonance imaging. - Results - Ejection fraction improved in G-CSF treated patients from 41.1±11.9% to 47.1±11.9% (3 months) and decreased slightly to 45.7±15.1% after 1 year. Ejection fraction also improved in the placebo group from 43.8±9.0% to 49.5±11.8% (3 months) and decreased slightly to 42.9±15.4% after 1 year (1 year MRI follow-up was performed in 23 out initial 44 patients). There was no significant difference between the two groups at any time point. Other parameters such as infarct size, myocardial perfusion, left ventricular end-diastolic and end-systolic volumes were not different between the two groups. Event-free survival of such as death, (re) myocardial infarction or acute coronary syndromes, coronary artery bypass grafting and target lesion revascularization was not significantly different between both groups. - Conclusions - G-CSF administration after sub-acute STEMI is feasible and safe but does not improve myocardial function or survival when used as a single substance.